2020
DOI: 10.1176/appi.ps.201900231
|View full text |Cite
|
Sign up to set email alerts
|

Using Continuous Quality Improvement to Design and Implement a Telepsychiatry Program in Rural Illinois

Abstract: Although telepsychiatry has emerged as an innovative tool for increasing access to behavioral health services, few studies have examined the complexities associated with designing and implementing telepsychiatry programs. This column examines a multisite, multimodal telepsychiatry program that has been providing direct care, synchronous consultation, and asynchronous consultation services in rural Illinois since 2016. The program used quality improvement metrics and implementation science strategies to improve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 5 publications
0
17
0
Order By: Relevance
“…These studies, largely in behavioral health-related settings, have demonstrated that the consumer experience is equivalent or superior to in-person encounters across a range of diagnoses, patient populations, and health care settings [ 7 , 9 - 11 ]. Moreover, under certain circumstances telemedicine is more cost-effective than in-person care and can allow health care entities to provide health care where it may otherwise be unavailable, either due to physical distance between the provider and patient or distance between a group of patients who can interact remotely but not in the same physical setting [ 7 , 12 - 14 ]. However, there has historically been a gap between the increasing research interest in telemedicine and its broad-scale implementation and acceptance by health systems due to reimbursement limitations, technical barriers, physician attitudes, and lack of physician education [ 15 , 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…These studies, largely in behavioral health-related settings, have demonstrated that the consumer experience is equivalent or superior to in-person encounters across a range of diagnoses, patient populations, and health care settings [ 7 , 9 - 11 ]. Moreover, under certain circumstances telemedicine is more cost-effective than in-person care and can allow health care entities to provide health care where it may otherwise be unavailable, either due to physical distance between the provider and patient or distance between a group of patients who can interact remotely but not in the same physical setting [ 7 , 12 - 14 ]. However, there has historically been a gap between the increasing research interest in telemedicine and its broad-scale implementation and acceptance by health systems due to reimbursement limitations, technical barriers, physician attitudes, and lack of physician education [ 15 , 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…It also discusses different approaches to mitigating challenges to implementations related to technology, patient and staff resistance, and clinician shortage. To our knowledge, this is one of few case studies reporting such an initiative and thus presents a timely contribution to the literature (Hossam Mahmoud et al 2020a , b ; Peter Yellowlees et al 2020 ). The value of telepsychiatry became exponentially more evident following the COVID-19 pandemic, and it is expected that more healthcare institutions will start adopting this modality to deliver mental health care moving forward (Naal et al 2020 ; Whaibeh et al 2020 ; Peter Yellowlees et al 2020 ).…”
Section: Discussionmentioning
confidence: 85%
“…The planning and implementation processes of this program have utilized many of the “core competencies” described in the literature as critical for telehealth implementation, including the utilization of implementation services that help in planning, training, education and implementation, as well as operations support, regulatory compliance, and teleclinician management (Adaji and Fortney 2017 ; Lokken et al 2019 ; H Mahmoud et al 2020a , b ; Naal et al 2020 ; Wang and Alexander 2014 ). While some of these services could have been implemented in-house, such as ensuring adequate support through a telehealth navigator and other clinical services, there was a significant value to partnering with a telepsychiatry organization that has experience with telepsychiatry implementation, for ongoing issue tracking, teleclinician training, teleclinician management, compliance, and legal support.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a study of psychiatric e-consult implementation at the University of California, San Francisco, e-consults were established first for eight other specialty areas before the implementation of psychiatric e-consults 18 . As another example, a largely rural health system in Illinois and Michigan first implemented video-based direct patient evaluations by psychiatrists and then live, synchronous PCP-to-psychiatrist consultations before implementing psychiatric e-consults 19 . It should be noted that psychiatric e-consults have been implemented in both contexts with co-located mental health services and those without, including in the same study 20 .…”
Section: Resultsmentioning
confidence: 99%